Random survival forest in determination of important risk factors on overall survival and disease-free survival in gastric cancer patients - M. Safari; M. Rahimi; J. Faradmal; B. Ghaderi; M. Anari; G. Roshanaei (World Cancer Research Journal, 2023)
Objective: Although the incidence of stomach cancer is decreasing in the world, its incidence is still high in Iran. Despite different treatments for cancer, disease recurrence, and death may occur in some patients. Various factors affect survival and recurrence after treatment. This study aims to identify factors affecting overall survival (OS) and disease-free survival (DFS) in patients with gastric cancer (GC) using a random survival forest (RSF).